Localization of Coated Iron Oxide (Fe3O4) Nanoparticles on Tomato Seeds and Their Effects on Growth - Lau, Elizabeth C.H.T.; Carvalho, Lucas B. [UNESP]; Pereira, Anderson E.S. [UNESP]; Montanha, Gabriel S.; Corrêa, Camila G.; Carvalho, Hudson W.P.; Ganin, Alexey Y.; Fraceto, Leonardo F. [UNESP]; Yiu, Humphrey H.P. (American Chemical Society (ACS), 2020)
Food demand due to the growing global population has been stretching the agriculture sector to the limit. This demands the cultivation of plants in shrinking land areas which makes the search for highly effective systems for plant nutrition and pest control important. In this context, the application of nanoparticles (NPs) in agriculture can have a transformative effect on food production techniques as it can enable the delivery of bioactive agents (including growth factors, pesticides, and fungicides) directly to plants. Herein, we report the application of unfunctionalized as well as amine-functionalized and polycaprolactone-coated Fe3O4 NPs to seed treatment in tomato (Solanum lycopersicum). The study reveals that the treatment has no side effects on plant germination and development. Furthermore, the translocation of NPs in seeds and seedlings posttreatment depends on the surface functionalization of the NPs. X-ray fluorescence spectroscopy analysis of seedlings suggested that around 66% of unfunctionalized Fe3O4 NPs were translocated in the cotyledons, while only 50% of functionalized NPs (both amine and polycaprolactone) were translocated. Our results demonstrate that all particles were taken up by the seeds, thus suggesting that the functionalized NPs can act as a versatile platform for delivering of active compounds, such as fungicides and growth factor agents.
Keywords: agriculture; APTES; delivery; magnetite; polycaprolactone; seedling; silanization; μ-XRF